(untitled) (Revista Latino-Americana de Enfermagem, 2003)
This study was carried out at the Pediatrics Unit in a School Hospital of the city of São Paulo during the second semester of 2000. This is a qualitative research with the following objectives: (1) to understand how mothers with a child in hospital identify the nurse as well as other components of the nursing Staff (technicians and assistants) and (2) to learn about their perceptions about the care provided by the nursing staff. Eight mothers with a child hospitalized were individually interviewed. Speeches were submitted to a thematic analysis of the content. Two categories were observed: Identification of the nurse/nursing staff by mothers with a child in hospital and the perception of these mothers about the nursing staff. In the first category, the difficulty to identify the components of the nursing staff was observed. In the second, it was observed that the nursing activity is seen as subordinated to the medical area. Eventually, mothers have difficulty to distinguish what is performed by the nurse or by the other members of the staff but the entire nursing care is evaluated as very good. Besides, the nurse is considered as the one who solves the problem. Nursing is seen by these mothers as an activity mediated by the representation of motherhood. The care performed by this staff in spite of being considered as very good, still needs to be presented to mothers as professionals and self-employed in order to change a stereotyped view of nursing.